Implementasi Undang Undang Ketenagakerjaan Dalam Penjanjian Kerja Antara Perusahaan Dengan Karyawan Di PT. Sentosa Hastareksa - Alvina Yusi Rahman; Fahra Khoerunisa; M Abby Akbar; Resti Nur Alvianti; Sri Maesin Mu’awaroh; Resya Dwi Marselina (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
A work agreement is an agreement or agreement made between a trade union that has been registered with the Department of Manpower and an entrepreneur who is a legal entity, which solely contains work conditions that must be taken into account in the work agreement. The formulation of the problem is how the implementation of employment agreements in joint stock companies is taken into account by labor laws and regulations, and whether the employment agreements made with employees of the joint stock company PT. Sentosa Hatareksa fulfill the elements of employment work agreements. Work agreement according to Law Number 13 of 2003 concerning Employment. Research methods include: library research and field research. From the survey results, it was concluded that there are still several companies that continue to provide arguments supporting employment agreements between companies and workers that violate Employment Law no. 13 of 2003, namely if a company does not pay its employees' leave, does not retire or fails, the employee is entitled to compensation according to law.